Length of College Service Experience Effect on Future Life Over Time - Susan Gamble; Allison Nichols; Margaret Miltenberger; Kelly Hicks; Shirley Wilkins (The University of Alabama, 2022)
The college experience offers many opportunities for students to become engaged in service activities. Most studies about these activities have been conducted on populations of students who have either just completed their service activity or just graduated from college. Inconsistent findings on how the length of service activities during college influence choices later in life have left researchers unsure of the value in lengthening service opportunities. To determine if the length of service makes a difference on benefits associated with service, an online survey of 277 former college student volunteers ranging in age from 21 to 71 was completed. Findings showed a positive effect with the length of service on future service attitudes, dispositions, and behavior. The study found that as the length of the time period volunteers served for one organization in college increased, the more likely they were to give service later in life, value giving service to others in need, and believe they could make a difference in their community.